MARKETING STRATEGY IN INCREASING SALES VOLUME OF TEMPE MSMES AT SIMPANG LIMUN MEDAN MARKET - Ramazani Ramazani; Dewi Shinta Wulandari Lubis (SEAN Institute, 2023)
Tempe MSMEs Mr. Sinaga who is an MSMEs engaged in the food industry which produces processed tempeh wrapped in plastic and wrapped in banana leaves. This Tempe MSMEs is located at Jalan Santun No 70A, Sudirejo I Village, Medan Kota District, Medan City. The purpose of this study was to determine the marketing strategy for Mr. Sinaga's Tempe MSME in order to increase sales at the Medan intersection market. Tempe MSMEs Mr. Sinaga implements the 4P components of the Marketing Mix product (product), place (place), price (price), and promotion (promotion). This studies is a sort of subject studies, specifically the writer is going without delay to the sector at Tempe MSMEs, Mr. Sinaga, Sudirejo I Village, Medan City District. The author uses data analysis strategies, specifically qualitative methods with a descriptive technique. In analyzing the facts, researchers performed field observations, interviews and documentation to obtain the required data. The results of this study indicate that the application of a marketing strategy to Mr. Sinaga's Tempe MSMEs by implementing the 4P components of the advertising blend in increasing sales volume with the result of increasing sales to Tempe MSMEs by setting prices according to product quality and target market. The role of place in increasing Tempe MSMEs is choosing a strategic location and center of community outreach for shopping at the market. The promotion carried out by Tempe MSMEs is to increase sales, namely by cooperating with other traders, maintaining regular customers and marketing face to face around the market.